2020
DOI: 10.1002/alr.22646
|View full text |Cite
|
Sign up to set email alerts
|

Management of chronic rhinosinusitis with steroid nasal irrigations: A viable nonsurgical alternative in the COVID‐19 era

Abstract: Background High‐dose, high‐volume steroid nasal irrigations (NSI) have been incorporated into the medical management of recalcitrant CRS, primarily following surgical intervention. The objective of this study was to evaluate the role of NSI as a preoperative management and to identify the percentage of patients who ultimately underwent ESS for recalcitrant CRS despite being on NSI. Methods Retrospective chart review of patients presenting with CRS who underwent a trial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Some fear discontinuing INCS may not only worsen symptoms but increase viral shedding due to coughing and sneezing. High volume nasal steroids are particularly efficacious in the treatment of CRS without necessitating surgical intervention 2492,2493 . One randomized, controlled trial in CRSsNP patients without history of sinus surgery showed greater improvements in SNOT‐22 and Lund‐Kennedy scores after using mometasone nasal irrigations compared to mometasone nasal spray for 8 weeks 2492 .…”
Section: Crs Management In the Context Of Covid‐19mentioning
confidence: 99%
“…Some fear discontinuing INCS may not only worsen symptoms but increase viral shedding due to coughing and sneezing. High volume nasal steroids are particularly efficacious in the treatment of CRS without necessitating surgical intervention 2492,2493 . One randomized, controlled trial in CRSsNP patients without history of sinus surgery showed greater improvements in SNOT‐22 and Lund‐Kennedy scores after using mometasone nasal irrigations compared to mometasone nasal spray for 8 weeks 2492 .…”
Section: Crs Management In the Context Of Covid‐19mentioning
confidence: 99%
“…7 Corticosteroid irrigations have shown benefit in reducing the need for endoscopic sinus surgery (ESS) with 64% of surgery candidates avoiding the operating room in one recent pilot study. 21 Failure of this medication leads to treatment escalation to interventions such as ESS, steroid-eluting stents, or biologics, all of which are significantly more expensive than intranasal corticosteroids. 1 The overall economic burden of CRS is immense: direct and indirect annual costs in the United States are estimated to be $10 to $13 and $20 billion, respectively.…”
Section: Discussionmentioning
confidence: 99%
“… 50 In a retrospective study, 64.4% of all patients with CRS treated with nasal steroid irrigations did not require surgical management after treatment for at least 6 weeks. 51 These studies are preliminary but promising given the likely prolonged COVID-19 environment.…”
Section: Treatment Of the Rhinologic Patient In The Coronavirus Diseamentioning
confidence: 97%
“…Recent studies have shown efficacy in the use of high-volume nasal steroid irrigations in patients with CRS who had not previously undergone surgery. 50 , 51 A double-blinded, randomized controlled trial in CRS without nasal polyposis patients without prior surgical intervention demonstrated clinically meaningful improvement in SNOT-22 scores with high-volume nasal steroid irrigations compared with steroid sprays. 50 In a retrospective study, 64.4% of all patients with CRS treated with nasal steroid irrigations did not require surgical management after treatment for at least 6 weeks.…”
Section: Treatment Of the Rhinologic Patient In The Coronavirus Diseamentioning
confidence: 99%